Changes in courtship behaviour following rejection: The influence of female phenotype in Drosophila melanogaster. (21st December 2017) - Balaban‐Feld, Jesse; Valone, Thomas J.
Abstract: Courtship can be costly and so selection should favour individual males that reduce courtship towards female types that have a low probability of resulting in copulation. One way males can do this is by associating previous courtship failure with the traits of particular rejecting females. We characterised changes in male Drosophila melanogaster courtship behaviour following a failed mating attempt with one of the four female phenotypes that varied in size, age or mating status. To do this, we assessed individual courtship behaviour for each male presented again with a female of the same phenotype that previously rejected him. Males reduced subsequent courtship most strongly for recently mated (sexually non‐receptive) females. More interestingly, males also significantly reduced courtship activity following a failed mating experience from old females but did not do so for control (large, young, virgin) or small females. As such, males significantly reduced courtship towards both female types possessing chemical cues associated with their phenotype (age and mating status), but not towards a female phenotype based on physical characteristics (body size). Our results suggest that males are able to modify their courtship behaviour following experience, but that they are better prepared to associate chemical traits that may be more reliable indicators of the likelihood of courtship failure.